Is there a significant relationship between the empowering leadership behaviors of school principals and the psychological resilience of teachers? Understanding the moderating effects of gender and length of time spent with the school principal - Mehmet Sabir Çevik; Emine Doğan (BMC Psychology)
Abstract The psychological resilience of teachers has gained significant attention due to its positive effects on schools and students. This cross-sectional quantitative study investigates the moderating roles of gender and the length of time spent with the school principal in the relationship between principals' empowering leadership behaviors and teachers' psychological resilience. Data were collected from 362 teachers working in public primary, secondary, and high schools in Siirt, Türkiye. Descriptive statistics, correlation analysis, and moderation analysis using the bootstrapping method were applied to analyze the data. The findings reveal that the empowering leadership behaviors of school principals positively correlate with teachers' psychological resilience, with variations based on gender and time spent with the principal. Specifically, the relationship is stronger for female teachers compared to male teachers and for those who have spent more time with the school principal. These results offer theoretical insights and practical recommendations for enhancing teacher resilience through leadership practices, highlighting the importance of understanding contextual and demographic factors.